Iowa RBA, February 16, 1998 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1998)
Email for the Iowa RBA for February 16, 1998. Highlights include waterfowl, Gulls, Redpolls, Prairie Falcon and Varied Thrush. Includes hand written notes in preparation for next week's update. Epson - sheet feed/flatbed